2018
DOI: 10.1016/j.celrep.2018.10.078
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Tau via an Unconventional Non-vesicular Mechanism

Abstract: Highlights d ATP-independent unconventional secretion of Tau directly through the plasma membrane d Phosphorylated oligomeric Tau clusters in plasma membrane microdomains d Tau secretion can be manipulated by changing plasma membrane properties d Heparan sulfate proteoglycans facilitate unconventional secretion of Tau

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
182
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 57 publications
(58 reference statements)
5
182
0
Order By: Relevance
“…Tau localizes to the PM in a clustered manner, and this localization is enhanced by overexpression or hyperphosphorylation, possibly as a consequence of increased levels of cytosolic tau or enhanced aggregation. Transmission electron microscopy revealed two types of tau clusters, with diameter ranging between 50 and 200 nm, at or very close to the PM [159]. Similar, reversible cation-sensitive clustering of tau has been previously reported for recombinant human tau in supported brain lipid membranes [161].…”
Section: Tau Secretion Directly Through the Plasma Membranesupporting
confidence: 82%
See 1 more Smart Citation
“…Tau localizes to the PM in a clustered manner, and this localization is enhanced by overexpression or hyperphosphorylation, possibly as a consequence of increased levels of cytosolic tau or enhanced aggregation. Transmission electron microscopy revealed two types of tau clusters, with diameter ranging between 50 and 200 nm, at or very close to the PM [159]. Similar, reversible cation-sensitive clustering of tau has been previously reported for recombinant human tau in supported brain lipid membranes [161].…”
Section: Tau Secretion Directly Through the Plasma Membranesupporting
confidence: 82%
“…Several studies suggest that while a fraction of the total extracellular tau is indeed found in exosomes or ectosomes, a large fraction of the extracellular tau pool exists in vesicle-free form [149,155,157,158] (Table 2). Two recent studies demonstrated that tau secretion can occur via a type I mechanism of unconventional protein secretion (UPS I), i.e., by direct translocation across the PM [67,159]. Using complementary methodological approaches, both groups concluded that direct secretion of tau through the PM involves the following key steps: (1) recruitment and clustering of tau at the cytosolic leaflet of the PM involving hyperphosphorylation of tau and specific lipids such as phosphatidyl inositol 4,5 phosphate (PI(4,5)P 2 ) cholesterol and sphingolipids, and (2) release from the PM facilitated by binding to heparan sulfate proteoglycans (HSPG) located at the extracellular leaflet of the PM (Fig.…”
Section: Tau Secretion Directly Through the Plasma Membranementioning
confidence: 99%
“…In previous studies, it has been proven the seeding nature of Tau as it causes template-dependent aggregation on uptake by healthy neurons [11]. The aggregated extracellular Tau species secreted by various mechanisms have tendency to propagate the disease [41][42][43]. The use of other omega-3 fatty acids DHA, EPA has been studied for the uptake of extracellular Aβ-plaques and their clearance [14,44].…”
Section: Discussionmentioning
confidence: 99%
“…Along with the well-established role for PI(4,5)P2 in unconventional secretion of HIV-Tat 30,31 , these findings point at a shared secretory mechanism between FGF2 and HIV-Tat. Furthermore, with Tau and Interleukin 1β, two additional extracellular factors secreted by unconventional means, even more examples have been reported for unconventional secretory processes that depend on PI(4,5)P2 as a prerequisite for their transport into the extracellular space [27][28][29]32 . Thus, after decades of research on unconventional secretory mechanisms in mammalian cells, common features between pathways that are taken by proteins functionally as different as FGF2, Interleukin 1β, Tau and HIV-Tat are beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a role for PI(4,5)P2 has been reported for unconventional secretion of Tau, HIV-Tat and Interleukin 1β [26][27][28][29][30][31] . In addition, in case of Tau, sulfated glycosaminoglycans on cell surfaces have been shown to have a critical function in trans-cellular spreading that is mediated by unconventional secretion of Tau from donor cells 27,32 .…”
Section: Introductionmentioning
confidence: 99%